ΣΟΦIA in 1 Corinthians - Goulder, Michael Douglas (New Testament studies, 1991)
1 Corinthians presents many problems, whose difficulty consists in large measure in their interrelatedness; but the major problem of the first four chapters is the nature of the σοφία against which Paul polemicizes. This is especially mysterious because the apostle treats it with unquestionable seriousness, and yet it does not apparently recur in any other letter, not even in 2 Corinthians. As it is so closely linked in the text with the σχίσματα which are the topic of 1.12–17, 3.1–17 and 3.22–3, if not other verses, it is necessary to begin with a brief discussion of that question.